Pemanfaatan Limbah Kotoran sapi Menjadi Biogas Sebagai Sumber Energi Listrik di Dusun Tegalmulyo, Kecamatan Bungatan, Situbondo - MOH MUFID; Ellya Dwi Lestari; Nugroho Jerry Kurniawan; Nurul Nikmah; Ignas Oni Faentaono; Dafit Ari Prasetyo; Dety Oktavia Sulistiono; Azamataufiq Budiprasojo (P3M Politeknik Negeri Jember, 2026)
Electricity is a basic need, but access to electricity in remote areas remains limited due to geographic and infrastructure constraints. Tegalmulyo Hamlet, dominated by cattle farming, has traditionally disposed of manure waste without optimal utilization, thereby polluting the environment. This community service activity aims to process cow dung waste into electrical energy through a community-based Biogas Power Plant (PLTBg). The approach used is Participatory Rural Appraisal (PRA), which actively involves the community in the planning, construction, and management of the system. A 1 m³ digester installation produces a potential biogas of 8.65 m³/day, with a theoretical electrical energy of approximately 96.6 kWh per day. In implementation, energy utilization is adjusted to the capacity of a 1 kW generator, thus meeting the electricity needs of 1,866 Wh per day for street lighting, livestock pens, and one resident's home. This program not only provides renewable energy but also reduces environmental pollution and produces organic fertilizer from biogas residue.